Analisis Penyelesaian Sengketa Harta Bersama dalam Perkawinan: Perspektif Hukum Keluarga Islam - Dyah Ayu Vijaya Laksmi; Syukron Nur Aziz; Kodrattullah Sidiq (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
The resolution of joint property disputes remains a critical challenge within Indonesia’s religious court system, particularly in divorce cases. This research explores the application of justice and legal certainty principles in the division of joint marital assets at the Metro Religious Court. Employing a descriptive qualitative approach, data were collected through in-depth interviews, courtroom observations, and the analysis of court rulings on 20 selected cases. Findings reveal that 60% of disputes were successfully resolved through mutual agreements facilitated by judges acting as mediators, while the remaining 40% required judicial rulings due to unsuccessful mediation. The effectiveness of consensus-based settlements is closely linked to mediation skills, the willingness of parties to compromise, and their understanding of rights and obligations. These results highlight the relevance of syura and tahkim principles in Islamic family law as effective foundations for achieving fairness and mutual benefit. The study recommends strengthening judges’ mediation capacities, developing technical guidelines for resolving joint property disputes, and promoting broader public awareness of deliberation-based mechanisms to ensure more efficient, just, and maslahat-oriented resolutions.